A loan management system as web services: a case study on a microfinance institution. (1st January 2014) - Dagba, Théophile K.; Lohounmè, Ercias; Nambila, Ange; Boco, Charbel Y.
Despite the determination of small microfinance institutions to expand into rural areas, they are limited by geographical isolation and high transaction costs. To set those institutions and their customers free from geographical constraints, we suggest isolated populations access some features of the enterprise application via Smartphone. This solution is based on a service-oriented architecture in which the main features are developed as web services. The invocation of the methods is performed from a Smartphone or a personal computer (PC), while the execution will be done on a server that returns an understandable result through web service description language (WSDL) generated by web services, where the transport is provided by simple object access protocol (SOAP).